(untitled) (Damu Journal of Sport Sciences, 2025)
The research problem lies in the fact that there is variation and fluctuation in the level of achievement in middle-distance running in Iraq during local and international championships, including the 1500m event. The research aimed to: develop training sessions using various surfaces and identify the effect of these exercises on the physiological adaptations of the kidneys in 1500m runners, as well as to identify the differences between the experimental group and the control group in the pre- and post-tests. Regarding the research methodology and field procedures, the researchers used the experimental approach because it was compatible with the nature of the research problem. They also chose to design a two-group equivalent (experimental and control) design. The research community was determined from among the (8) young athletes in Najaf Governorate who competed in middle-distance running for the 2023-2024 sports season. They were randomly divided into two groups. The most important conclusions were: Exercises using various surfaces (grass, asphalt, and sand), which included numerous applications, had a significant impact on raising the level of kidney adaptations among 1500m runners.